The Forgotten Mughals : A History of the Later Emperors of the House of Babar (1707-1857) - Cheema, G. S. (Brill | Manohar Publishers & Distributors, 2024)
A hundred and fifty years lie between the death of Aurangzeb and the final extinction of the Mughal empire. In its first hundred and fifty years the empire had seen six rulers, but during the next century and a half the Qila-i-Mualla would witness the passage of as many as eleven emperors-if one leaves out the six or seven failed pretenders. It was a period of violence and disorder, with armies constantly on the march across a landscape of increasing misery, impoverishment and desolation. The Forgotten Mughals is the story of these largely pageant emperors with their increasingly ineffectual ministers, and their gradual decline into irrelevance while younger and more powerful forces, both Indian and foreign, grappled with each other for the mastery of Hindostan. The landmark events like the wars of succession, the dictatorship of the Syed brothers, the Nadir Shahi and Durrani invasions with their attendant horrors, the bloodbath of Panipat and the final sack of Delhi in 1857 are all covered in detail. The book's strength lies in its anecdotal details, like that of young Muhammad Shah, hiding behind the ample skirts of the formidable Sadr un-Nissa, superintendent of the harem, and of Bidar Dil cowering in a closet, while the emissaries of Qutb-ul-Mulk tried, in vain, to convince his women that they had, in fact, come to call him to the throne. And who will believe today that, as part of the 'retributive justice' of the British, for nearly twenty years the Zinat masjid in Daryaganj was used as a bakery, and that the basement of the Fatehpuri mosque was sold to Seth Chuna Mall?